Analysis of the Current Situation of Teachers’ Mental Health in Higher Vocational Colleges - Gao, Xiaohui (Journal of Education and Educational Technologies, 2023)
This paper analyzes the psychological health status of teachers in higher vocational colleges, the existing psychological problems and the factors affecting their psychological health from the aspects of their living conditions, economic income, family conditions, working environment, etc. This has also become the source of their pressure and presents a more serious situation. Therefore, the search for solutions to the mental health problems of teachers in higher vocational colleges is not only related to their personal work enthusiasm, living standards and mental health, but also directly related to their attitude towards life and work. A person who is physically and mentally healthy will be full of vitality and vitality, work hard, and work efficiency will not be poor. The psychological health of teachers is closely related to the growth of students. As a preacher, the heavy responsibility of teachers is extremely arduous. This is due to the characteristics of this special profession itself, which can not tolerate carelessness. This requires their psychological endurance to be strong enough. Teachers also have their own family and living space, and they should constantly change their identity in work and life.